2009
DOI: 10.1111/j.1567-1364.2009.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida siamensissp. nov., an anamorphic yeast species in theSaturnisporaclade isolated in Thailand

Abstract: Three strains of a novel anamorphic yeast species were isolated from natural samples collected in Thailand, including strain EF10 isolated from sediment in a mangrove forest, strain ST-473 from rotten wood, and strain ST-479 from a wild mushroom (Hygrophorus sp.). Analysis of the D1/D2 domains of the large-subunit rRNA gene sequence revealed that the sequence of strain EF10 differed from the other two strains (ST-473 and ST-479), which had identical sequences, by only one nucleotide (nt) substitution in 535 nt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Species described later in the genus Spathaspora include Spathaspora arborariae (Cadete et al, 2009), Spathaspora brasiliensis, Spathaspora roraimanensis, Spathaspora suhii and Spathaspora xylofermentans (Cadete et al, 2013). Five anamorphic Candida species, namely Candida jeffriesii, Candida lyxosophila, Candida materiae, Candida subhashii and Candida xylanilytica, are also related to this genus as indicated by phylogenetic analyses of the D1/D2 domains of the large subunit (LSU) rRNA gene (Boonmak et al, 2011;Cadete et al, 2013). Species of the Spathaspora clade are associated with rotting wood or insects linked with this substrate (Boonmak et al, 2011;Cadete et al, 2009Cadete et al, , 2013Nguyen et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Species described later in the genus Spathaspora include Spathaspora arborariae (Cadete et al, 2009), Spathaspora brasiliensis, Spathaspora roraimanensis, Spathaspora suhii and Spathaspora xylofermentans (Cadete et al, 2013). Five anamorphic Candida species, namely Candida jeffriesii, Candida lyxosophila, Candida materiae, Candida subhashii and Candida xylanilytica, are also related to this genus as indicated by phylogenetic analyses of the D1/D2 domains of the large subunit (LSU) rRNA gene (Boonmak et al, 2011;Cadete et al, 2013). Species of the Spathaspora clade are associated with rotting wood or insects linked with this substrate (Boonmak et al, 2011;Cadete et al, 2009Cadete et al, , 2013Nguyen et al, 2011).…”
mentioning
confidence: 99%
“…Five anamorphic Candida species, namely Candida jeffriesii, Candida lyxosophila, Candida materiae, Candida subhashii and Candida xylanilytica, are also related to this genus as indicated by phylogenetic analyses of the D1/D2 domains of the large subunit (LSU) rRNA gene (Boonmak et al, 2011;Cadete et al, 2013). Species of the Spathaspora clade are associated with rotting wood or insects linked with this substrate (Boonmak et al, 2011;Cadete et al, 2009Cadete et al, , 2013Nguyen et al, 2011). Most species of the clade, such as C. jeffriesii, C. lyxosophila, Spathaspora arborariae, Spathaspora brasiliensis, Spathaspora passalidarum, Spathaspora roraimanensis, Spathaspora suhii and Spathaspora xylofermentans, are known for their ability to ferment D-xylose.…”
mentioning
confidence: 99%
“…Six anamorphic Candida species, C. diversa, C. sanitii, C. sekii, C. siamensis, C. silvae and C. suwanaritii, are also related to this clade (Morais et al 2005;Kurtzman 2006;Boonmak et al 2009;Limtong et al 2010). Most species of Saturnispora were isolated from plant-related substrates, soil, and water samples.…”
Section: Introductionmentioning
confidence: 97%
“…Most species of Saturnispora were isolated from plant-related substrates, soil, and water samples. These yeasts are characterized by the fermentation and assimilation of only a few carbon compounds and are almost indistinguishable physiologically from one another (Kurtzman 2006;Boonmak et al 2009;Limtong et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Species of this genus have been isolated from various sources in terrestrial and aquatic habitats. In recent years, many novel Candida species have been described from strains isolated in Thailand, Taiwan, and Japan from various natural samples, e.g., soils, estuarine waters, sediments in mangrove forests, insect frasses, and beetle galleries (Boonmak et al 2009;Endo et al 2008;Limtong et al 2007bLimtong et al , 2008Limtong et al , 2010Liu et al 2008;Nakase et al 2009). Phylogenetic analysis showed that these novel species are distributed in various clades, e.g., Ambrosiozyma, Metschnikowia, Pichia, Saturnispora, Wickerhamomyces, and Yarrowia.…”
Section: Introductionmentioning
confidence: 99%